Educate in times of pandemic: knowledge from complexity - Morales Díaz, José David; Sánchez Bautista, María Patricia; Esparragoza Bermejo, Nancy Silvia (IE Revista de Investigación Educativa de la REDIECH, 2021)
The present work characterizes the experiences of three teachers in times of pandemic in the context of primary education in Puebla, Mexico, who experienced changes in their way evaluating and imparting the concept of teaching boys and girls. A question arises from this study: “What is the new educational knowledge in times of pandemic?”, and it is related to qualitative methodology and grounded theory design; to obtain the information, interviews are carried out through podcast; the topics and incidences of teachers and directors are organized into categories: the purpose of education in the pandemic; transformation of the school since the pandemic began; the role of school staff in times of pandemic. From the ideas of the complexity of Edgar Morin, the results are associated where the development of responsibility, the human element as an act of respect for life, tolerance, ethics, the right to educate in the face of emerging situations from the use of new synchronous and asynchronous forms in teaching and learning result from the integration of knowledge.